2020
DOI: 10.3389/fmicb.2020.01529
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Factor Essential for Unconventional Secretion of Chitinase Cts1

Abstract: Subcellular targeting of proteins is essential to orchestrate cytokinesis in eukaryotic cells. During cell division of Ustilago maydis , for example, chitinases must be specifically targeted to the fragmentation zone at the site of cell division to degrade remnant chitin and thus separate mother and daughter cells. Chitinase Cts1 is exported to this location via an unconventional secretion pathway putatively operating in a lock-type manner. The underlying mechanism is largely unexplored.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 52 publications
2
34
2
Order By: Relevance
“…Microscopic analysis revealed that, as expected, the regulated strains grew yeastlike without any morphological phenotype both in glucose and in arabinose-containing media. However, in contrast to previous localization studies [24], Jps1-Gfp mainly formed intracellular aggregates (about 80%) during all stages of cytokinesis, with only a minor population of about 3% showing the expected localization in the fragmentation zone in late cytokinesis when transcription was induced by arabinose ( Fig. 2B).…”
Section: Evaluating Jps1 As a Regulator For Unconventional Protein Excontrasting
confidence: 99%
See 3 more Smart Citations
“…Microscopic analysis revealed that, as expected, the regulated strains grew yeastlike without any morphological phenotype both in glucose and in arabinose-containing media. However, in contrast to previous localization studies [24], Jps1-Gfp mainly formed intracellular aggregates (about 80%) during all stages of cytokinesis, with only a minor population of about 3% showing the expected localization in the fragmentation zone in late cytokinesis when transcription was induced by arabinose ( Fig. 2B).…”
Section: Evaluating Jps1 As a Regulator For Unconventional Protein Excontrasting
confidence: 99%
“…The presence of the potential anchoring factor Jps1 is essential for unconventional Cts1 secretion via the fragmentation zone (Fig. 1B, C) [24]. This mechanistic insight might provide the unique possibility of using Jps1 as a regulator for unconventional protein secretion and thus, to establish a first inducible system.…”
Section: Evaluating Jps1 As a Regulator For Unconventional Protein Exmentioning
confidence: 77%
See 2 more Smart Citations
“…Recently, we obtained the first insights into the cellular mechanism of unconventional secretion [ 29 , 30 , 31 ]. During cytokinesis of yeast cells, a primary septum is formed at the mother cell side, followed by a secondary septum at the daughter cell side, delimiting a so-called fragmentation zone ( Figure 1 A) [ 32 ].…”
Section: Introductionmentioning
confidence: 99%